Polarity Establishment and Maintenance in Ascidian Notochord - Peng, Hongzhe; Qiao, Runyu; Dong, Bo (Frontiers in Cell and Developmental Biology, 2020)
Cell and tissue polarity due to the extracellular signaling and intracellular gene cascades, in turn, signals the directed cell behaviors and asymmetric tissue architectures that play a crucial role in organogenesis and embryogenesis. The notochord is a characteristic midline organ in chordate embryos that supports the body structure and produces positioning signaling. This review summarizes cellular and tissue-level polarities during notochord development in ascidians. At the early stage, planar cell polarity (PCP) is initialized, which drives cell convergence extension and migration to form a rod-like structure. Subsequently, the notochord undergoes a mesenchymal-epithelial transition, becoming an unusual epithelium in which cells have two opposing apical domains facing the extracellular lumen deposited between adjacent notochord cells controlled by apical-basal (AB) polarity. Cytoskeleton distribution is one of the main downstream events of cell polarity. Some cytoskeleton polarity patterns are a consequence of PCP: however, an additional polarized cytoskeleton, together with Rho signaling, might serve as a guide for correct AB polarity initiation in the notochord. In addition, the notochord’s mechanical properties are associated with polarity establishment and transformation, which bridge signaling regulation and tissue mechanical properties that enable the coordinated organogenesis during embryo development.